132 Covid as a driver of change: leadership opportunities to implement novel ways of working in the surgical assessment unit of a district general hospital. (16th November 2020) - Court, Emma Louise; Lennon, Nicola Louise; Zarka, Anas; Alexander, Roderick
Abstract : Introduction: Covid restrictions provided opportunities for novel approaches to patient assessment in the right place at the right time, whilst minimising unnecessary footfall in the Surgical Assessment Unit (SAU) of a UK District General Hospital. Prior to the pandemic, referrals were taken by Nurse Coordinators. Increasing call volumes put pressure on the department & disrupted clinical duties. Referrers often expressed difficulties in contacting SAU. 'Hot Clinics' (HC) reviewed patients attending the Emergency Department (ED) who did not require admission. Shielding Registrars led an innovative approach to triage SAU referral calls from General Practitioners (GP) & Nurse Practitioners (NP). Aims: To give Registrars an opportunity to innovate & lead service development through a novel way of working to triage SAU telephone referrals. Methods: Referral calls were diverted for triage by the hospital switchboard. Three outcomes were offered: Clinical advice, HC appointment or SAU review. Prospective referral data (15/6–31/7/2020) & retrospective non-triage data (15/6–1/7/2019) were gathered. Triage effects were measured by outcome comparison with non-triage data. Questionnaires were emailed to stakeholders. Results: From 15/6–1/7/2019, 56% of patients reviewed in SAU were sent home & 44% admitted, compared to 23.6% & 28.1% of referrals during the 2020 study period. Furthermore, 28.4% of admissions were avoided by triage. Only 3.1% of patients triaged presented to ED within 7 days. Triage reduced disparity in admission rates for GP & NP referrals (53.6% & 16.2% in 2019, compared to 29.1% & 26% in 2020). HC availability was limited. In view of reduced admissions, expanding this may prove cost neutral. Triage was popular with stakeholders. Data will inform the Integrated Front Door project, to shape future development of Emergency Care. Conclusions: Traditional ways of working should be challenged. Novel approaches can be cost effective & positively impact patient care.